The Role of Livestock in Developing Communities Enhancing Multifunctionality - Moyo, Siboniso; Swanepoel, Frans; Stroebel, Aldo (UJ Press, 2010)
The book provides critical information and knowledge on the importance of livestock in the global effort to alleviate poverty and promote human health. It describes and evaluates case studies, examines theoretical frameworks, and discusses key global policy development issues, challenges and constraints related to smallholder livestock-production systems around the globe. The book is written for academic professionals, industry experts, government officials and other scholars interested in the facts and issues concerning the contribution of livestock to the social and economic progress of developing countries.